2021
DOI: 10.1007/s40123-021-00396-5
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Symptoms After Monocular SMILE: A Contralateral Eye Study

Abstract: Introduction: To investigate nighttime symptoms in patients with myopic anisometropia after monocular small incision lenticule extraction (SMILE) surgery. Methods: Thirty-six patients who had undergone monocular SMILE more than 6 months previously were recruited at the Eye & ENT Hospital of Fudan University. The average age at surgery was 25.4 ± 6.1 years. Preoperative spherical equivalent (SE) was -3.77 ± 1.56 D in SMILE-treated eyes and -0.08 ± 0.66 D in unoperated eyes. Main measurements included uncorrecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…This study evaluated the visual outcomes after SMILE in the early stages and found that the safety index was 1.28 and the efficacy index was 1.20, indicating that SMILE surgery is safe and effective for high and low-to-moderate myopia. This result is consistent with the results of Zhao et al 20 and Miao et al, 21 and there is mounting evidence of the safety and efficacy of SMILE globally. [22][23][24] The disk halo size in HM and LM after SMILE manifested different characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study evaluated the visual outcomes after SMILE in the early stages and found that the safety index was 1.28 and the efficacy index was 1.20, indicating that SMILE surgery is safe and effective for high and low-to-moderate myopia. This result is consistent with the results of Zhao et al 20 and Miao et al, 21 and there is mounting evidence of the safety and efficacy of SMILE globally. [22][23][24] The disk halo size in HM and LM after SMILE manifested different characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…All SMILE procedures were performed by the same surgeon (XZ), and the procedural details were reported by Zhao et al 20 All surgeries were conducted using the VisuMax ® femtosecond laser platform (Carl Zeiss Meditec, Jena, Germany) with the cap diameter set to 7.5 mm, a cap thickness of 120 μm, a 6.1 to 6.8-mm lenticule diameter range, and an incision located at 12:00 with a 2-mm side cut for lenticule extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from these results, studies on changes in glare after femtosecond laser refractive surgery have demonstrated similar results [ 7 , 11 , 12 ]. A study of nighttime symptoms in SMILE-treated eyes were compared to those of unoperated eyes for the same patients, and no differences were noted in terms of halo size [ 9 ]. Moreover, Han et al investigated disk halo size (at 5 cd/m 2 ) at 1 week and 3 months after SMILE and reported that SMILE induced a significant increase in halo size at 1 week postoperatively but that no change was observed at 3 months postoperatively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [ 9 ], patients were tested unilaterally at a viewing distance of 2.5 m from the monitor (MonPack One, Metrovision, France) after 5 min of dark adaptation. Luminance conditions were consecutively set to 1, 5, and 100 cd/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The incidence and severity of night vision disturbances were evaluated using a questionnaire provieded in supplementary Table 1 which was adminstered by Zhao et al for measuring the visual quality of patients undergoing SMILE [ 17 ]. Recipients were asked to evaluate their current night vision disturbances (glare, halos, starburst and visual distortion) using a 4-level scale of none, mild, moderate, or severe.…”
Section: Methodsmentioning
confidence: 99%